Development of biocompatible Ni-ferrite nanoparticles with PEG-coated for magnetic hyperthermia - K. Ohara; T. Moriwaki; K. Nakazawa; T. Sakamoto; K. Nii; M. Abe; Y. Ichiyanagi (AIP Advances, 2023)
In this study, NiFe2O4 nanoparticles were prepared as a thermophilic agent for magnetic thermotherapy. To improve biocompatibility, the particles were coated with polyethylene glycol, which is hydrophilic and nontoxic; X-ray diffraction measurements confirmed that the particle size could be controlled to 3, 6, 9, and 17 nm. Fourier-transform infrared spectroscopy confirmed PEG modification to the particles. Biocompatibility with cells were improved by coating with PEG of high molecular weight. The heat-generating effect of the particles was investigated by measuring the magnetic susceptibility and temperature rise in an AC magnetic field. Furthermore, a device using a zero-voltage switching circuit was developed to generate heat. Finally, in vitro experiments using human breast cancer cells were successfully performed to confirm the onset of the hyperthermia effect.